Solid-Phase Synthesis of Difficult Purine-Rich PNAs through Selective Hmb Incorporation: Application to the Total Synthesis of Cell Penetrating Peptide-PNAs - Tailhades, Julien; Takizawa, Hotake; Gait, Michael J.; Wellings, Don A.; Wade, John D.; Aoki, Yoshitsugu; Shabanpoor, Fazel (Frontiers in Chemistry, 2017)
Antisense oligonucleotide (ASO)-based drug development is gaining significant momentum following the recent FDA approval of Eteplirsen (an ASO based on phosphorodiamidate morpholino) and Spinraza (2’-O-methoxyethyl-phosphorothioate) in late 2016. Their attractiveness is mainly due to the backbone modifications which have improved the in vivo characteristics of oligonucleotide drugs. Another class of ASO, based on peptide nucleic acid (PNA) chemistry, is also gaining popularity as a platform for development of gene-specific therapy for various disorders. However, the chemical synthesis of long PNAs, which are more target-specific, remains an ongoing challenge. Most of the reported methodology for the solid-phase synthesis of PNA suffer from poor coupling efficiency which limits production to short PNA sequences of less than 15 residues. Here we have studied the effect of backbone modifications with Hmb (2-hydroxy-4-methoxybenzyl) and Dmb (2,4-dimethoxybenzyl) to ameliorate difficult couplings and reduce “on-resin” aggregation. We firstly synthesized a library of PNA dimers incorporating either Hmb or Dmb and identified that Hmb is superior to Dmb in terms of its ease of removal. Subsequently, we used Hmb backbone modification to synthesize a 22-mer purine-rich PNA, targeting dystrophin RNA splicing, which could not be synthesized by standard coupling methodology. Hmb backbone modification allowed this difficult PNA to be synthesized as well as to be continued to include a cell-penetrating peptide on the same solid support. This approach provides a novel and straightforward strategy for facile solid-phase synthesis of difficult purine-rich PNA sequences.